Influência do fator de extração do café torrado e granulado e injeção de gás na formação de espuma no café solúvel tipo spray drier - Morales, Eduardo Vicentin (2014)
Coffee is the second most consumed product in the world, but its soluble form, although very practical, does not have good acceptance in the Brazilian market. Seeking to boost its consumption, this study aimed to increase the foam of soluble Spray Drier coffee in type subjected to variation of factor extraction and homogenization of the extract with compressed air during drying and to evaluate the relationship of carbohydrates, proteins and viscosity of the extract with foaming formation. The extraction factors used were 3, 4 and 5 and the amount of gas was limited to 5NL.min-1. The amount of dispersion time and foam density, color, moisture, particle size distribution and microstructural analysis of the dried product were evaluated. The carbohydrate content was determined by demonstrating an average result of 42.78 % with no statistical difference between the factors extraction and correlation with foam stability ISO 11292 method. The protein content was determined by the spectrophotometric method of Bradford demonstrating an average result of 11.24% with a statistical difference between the factors extraction and correlation with foam stability. The viscosity of the extracts was inversely proportional to the extraction factor. Coffee extracts with injection of gas and the use of homogenization showed better results in the amount of foam formed. Compressed air can be used to increase the amount of foam and the dried product directly influences the color and density of the product.